2017
DOI: 10.1186/s13690-017-0184-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of tuberculosis patients in nigist Eleni Mohammed general hospital, hosanna, southern nations, nationalities and peoples region, Ethiopia: a five year (June 2009 to August 2014) retrospective study

Abstract: BackgroundTuberculosis remains to be a major public health problem among under developed world due to delay in detection and treatment of patients with active TB. In Ethiopia, tuberculosis has been recognized as a major public health problem for more than fifty years.ObjectiveThe main objective of this study was to determine treatment outcomes and associated factors among TB patients attending Nigist Eleni Mohammed General Hospital, Hosanna, SNNPR, Ethiopia.MethodsA five years medical records on treatment outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
21
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 18 publications
8
21
4
Order By: Relevance
“…In addition, completing treatment successfully with respect to unsuccessful treatment outcome, the odds of completing treatment successfully was higher in patients with smear positive pulmonary TB and those tested negative for HIV, compared with their counterparts. In contrary, according to a study done in Nigist Eleni Mohammod General Hospital Hosanna, Ethiopia; those patients having smear-positive Pulmonary TB were more likely to had poor treatment outcomes compared with those patients having extra-pulmonary TB [7]. But, the other studies done in other parts of Ethiopia [15,20] and China [27] reported as there is no significant difference between treatment success rate and type of TB.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, completing treatment successfully with respect to unsuccessful treatment outcome, the odds of completing treatment successfully was higher in patients with smear positive pulmonary TB and those tested negative for HIV, compared with their counterparts. In contrary, according to a study done in Nigist Eleni Mohammod General Hospital Hosanna, Ethiopia; those patients having smear-positive Pulmonary TB were more likely to had poor treatment outcomes compared with those patients having extra-pulmonary TB [7]. But, the other studies done in other parts of Ethiopia [15,20] and China [27] reported as there is no significant difference between treatment success rate and type of TB.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the implementation of DOTS program, different reports across the country have indicated the existence of challenges in improving TB treatment outcomes. The challenges are emanated from differences in treatment-seeking behavior, poor compliance, presence of co-infection, variations in experts' qualification, and presence of drug resistance [7][8][9][10][11][12][13]. Due to these outcome differences, WHO in conjunction with the European Region of the International Union Against Tuberculosis and Lung Disease developed standardized categories to evaluate TB treatment outcomes [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…According to Federal Ministry of Health assessment in 2013/2014, DOTS program physical coverage reached 98.4% in hospitals and 79% health centers in the country (9). Nevertheless, different reports across the country have indicated the existence of challenges in treatment outcomes of TB patients despite the implementation of DOTS program (10, 11). Poor treatment-seeking behavior, incomplete treatment or poor compliance, treatment interruption, or default, a phenomenon that contributes to prolonged infectiousness and a higher risk of drug resistance, relapsed TB, and death, are the major challenges in DOTS program especially in resource-limited settings (12).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a study by Mohammed T et al and Gadoev J et al, noted that among the pulmonary TB patients who were registered during the study period, the majority 64.7% and 53% respectively were smear-negative. 7,20 Saroj et al, in 2010 demonstrated 10.41% were found positive for AFB by ZN staining. 21 Ben et al, showed that out of 221 sputum samples, 10.85% samples were positive with Ziehl-Neelsen staining.…”
Section: Resultsmentioning
confidence: 99%
“…Different studies have found similar results. In the study by Mohammed T et al, 84.8% were having pulmonary TB and 15.2% were having extra pulmonary TB 7. In a study by Pooja et al, (45.6%) had EPTB and at the Tuberculosis Clinic at the All India Institute of Medical Sciences, (AIIMS), New Delhi and the Sri Venkateswara Institute of Medical Sciences (SVIMS), Tirupati , patients with EPTB constituted 53% and 30.4% respectively during the period 1994-2002 8,9.…”
mentioning
confidence: 94%